1978
DOI: 10.1002/jez.1402060312
|View full text |Cite
|
Sign up to set email alerts
|

NA++K+‐ATPase in the osmoregulating clam Rangia cuneata

Abstract: Of six tissues sampled from the osmoregulating clam Rangia cuneata, mantle contained the highest concentration of Na++K+-ATPase activity and ouabain binding sites. Acclimation to low salinities was accompanied by adaptive increases in Na++K+-ATPase activity in mantle but not in gill. Since the number of ouabain binding sites did not show parallel increases, the mechanism of acclimation to reduced salinity in Rangia appears to involve activation of pre-existing pump sites in the mantle epithelium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

1979
1979
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(12 citation statements)
references
References 7 publications
0
12
0
Order By: Relevance
“…This is consistent with the relative role of this organ in ion regulation; marine species produce isosmotic urine (Cameron & Batterton, 1978;Cameron, 1979), whereas the crayfish antennal gland has a demonstrated ability to reabsorb electrolytes from the primary filtrate against a concentration gradient (Table 2). Increased renal Na + /K + -ATPase activity has similarly been associated with Na + retention in the process of hypo-osmotic urine formation in other aquatic vertebrates (Saintsing & Towle, 1978;Towle et al 1982). A parallel can again be seen with land crabs, which also possess high antennal gland ATPase activity, although their urine is isosmotic.…”
Section: Distribution Of Transport Enzyme Activitiesmentioning
confidence: 99%
“…This is consistent with the relative role of this organ in ion regulation; marine species produce isosmotic urine (Cameron & Batterton, 1978;Cameron, 1979), whereas the crayfish antennal gland has a demonstrated ability to reabsorb electrolytes from the primary filtrate against a concentration gradient (Table 2). Increased renal Na + /K + -ATPase activity has similarly been associated with Na + retention in the process of hypo-osmotic urine formation in other aquatic vertebrates (Saintsing & Towle, 1978;Towle et al 1982). A parallel can again be seen with land crabs, which also possess high antennal gland ATPase activity, although their urine is isosmotic.…”
Section: Distribution Of Transport Enzyme Activitiesmentioning
confidence: 99%
“…Although NKA activity was found in a range of tissues in the clam, Rangia cuneat (Saintsing and Towle, 1978), the highest activity was found in the mantle. NKA activity was also found to be highest in the mantle of the blue mussel, Mytilus galloprovincialis , while in another bivalve, Scapharca inasquivalvis , it was highest in the gills (Borgatti et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The NKA belongs to the P-type ATPase family and is essential for the regulation of cell osmolality (Lang et al, 1998;Li and Langhans, 2015). Saintsing and Towle (1978) revealed that the acclimation of the Atlantic rangia Rangia cuneata, a freshwater bivalve, to a low-salinity environment was accompanied by an adaptive increase in NKA activity in the mantle. In the Pacific abalone, the NKA activity of both the gills and mantle was significantly upregulated after individuals were transferred from 30 to 40 SW, which is a hyperosmotic salinity (Jia and Liu, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The Na + /K + -ATPase (NKA) is a vital active transporter that transports Na + and K + into cells; its action provides a driving force for the secondary transport of other inorganic ions and modulates cellular osmolality (Morth et al, 2011;Toyoshima et al, 2011). Relatively abundant NKA activity has been detected in the gills and mantle of bivalves (Saintsing and Towle, 1978;Borgatti et al, 2003). The NKA activity in the mantle of the clam Rangia cuneata is induced under hyperosmotic conditions (Saintsing and Towle, 1978).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation